Mobile services in banking sector: The role of innovative business solutions in generating competitive advantage - Rajnish Tiwari; Stephan Buse; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2007)
The wide-ranging economic developments of the previous decade, e.g. the integration of world economies, have made a significant impact towards increasing the mobility of the working populace and their families. At the same time, technological developments especially in the field of telecommunication have made it possible to offer innovative, location sensitive services on ubiquitous basis to customers on the move. Our paper examines innovative mobile solutions in the field of mobile financial services (MFS) by using four case studies from Germany and Switzerland - representing two banks and two different technology solutions. The paper scrutinizes the strategic relevance of MFS to the competitive position of the firm concerned. Finally, we present five propositions about the role of innovative business solutions in the banking sectors and recommend that a large scale empirical study to test these propositions be conducted in the future.
urn:nbn:de:gbv:830-opus-3294
Keywords: 650; Mobile Banking; Mobile Commerce; Mobile Financial Services; Multi-channel strategy; Innovation in banking sector